The Management of Park Equipment and Machinery Used in the Construction Industry and Housing Sector - Khayrullin Rustam (MATEC Web of Conferences, 2016)
The mathematical model was created, applicable to elaboration of options of development of a park of equipment and machinery used in construction industry, housing and utility management. The model based on solving the linear programming problem by means of simplex method. The mathematical model allows develop the rational plans and quasi optimal plans. The model is based on the created in the article the financial management algorithms of procurement and of repairs of equipment and machinery. The algorithms allow to take into account joint consideration of indicators of modernity and operability of equipment and machinery. The basic model is developed. The model is included into the automated planning system. It is used for planning and preparation of proposals of draft policy documents for development of park devices, equipment and machinery.